SURG-08. SARCOPENIA IS A PROGNOSTIC FACTOR OF 90-DAY MORTALITY AND OVERALL SURVIVAL IN ELDERLY PATIENTS WITH GLIOBLASTOMA. (12th November 2021) - Morshed, Ramin; Young, Jacob; Casey, Megan; Wang, Elaina; Aghi, Manish K; Berger, Mitchel; Hervey-Jumper, Shawn
Abstract: Elderly patients with glioblastoma (GBM) have worse overall prognosis compared to younger patients and are less likely to undergo tumor resection and adjuvant therapy. The goal of this study was to identify patient and treatment factors as well as preoperative imaging features associated with worse overall survival and death within 3 months of surgery in elderly GBM patients. A single-center retrospective study was conducted with patients who met the following inclusion criteria: 1) age ≥ 79 at surgery (past the average age of life expectancy), 2) underwent biopsy or resection of an IDH-wildtype WHO Grade IV GBM at the time of initial diagnosis, and 3) had no prior radiation or chemotherapy. Patient, imaging, and treatment data were collected retrospectively from the electronic medical record. Univariate and multivariate Cox proportional hazard and logistic regression analyses were performed to identify factors associated with overall survival and 90-day mortality. The cohort consisted of 110 patients with a mean age of 82.8 (range 79 to 94.1) at surgery and a median preoperative KPS of 80. Thirty-seven (33.6%) and 73 (66.4%) patients underwent biopsy and resection, respectively. Adjuvant chemo- and/or radiation therapy were used in 72.5% of cases. On multivariate analysis, age (HR 1.13 by year, p=0.01), increased masseter thickness (HR 0.88 by mm, p=0.049), adjuvant therapy (HR 0.05, p< .0001), and surgical resection rather than biopsy (HR 0.38, p=0.0007) were associated with improved survival. Decreased masseter thickness was the only preoperative factor on analysis that predicted 90-day mortality in the cohort (p=0.038). GBM patients past the average age of life expectancy still fare better when undergoing resection followed by adjuvant chemotherapy and radiation therapy. In addition to treatment factors that predict survival, smaller masseter diameter on preoperative imaging, a marker of sarcopenia, is associated with shorter survival and death within 90 days of surgery.